Practical Analysis Diagnosis And Treatment Of Nervous Diseases - Rita (Science Midwifery, 2022)
The nervous system is a network in the body that has various important functions for the body, while several body functions are controlled by the nervous system, including brain growth and development, sensation or perception, emotions, breathing and heart rate. The human nervous system is divided into two major parts, namely, the central nervous system and the peripheral nervous system. Many neurological diseases can become progressive, impairing respiratory function. Disorders due to neurological disease can affect the respiratory center, inspiratory / expiratory muscles, and upper respiratory tract muscles. Although neurological diseases have many causes and different clinical courses, in most cases respiratory complications are a major cause of morbidity and mortality. Often the first symptoms, respiratory disorders only in the form of sleep disturbances, and nocturnal desaturation. Examination of respiratory function by spirometry showed a restrictive picture with a fairly good total lung capacity. Management with a combination of assisted inspiration and expiration, accompanied by management of oral secretions, breathing exercises, and medical therapy. Good management can prolong survival, improve quality of life, improve cognitive function, reduce the incidence of pneumonia and hospitalization. The presence of an expert reveals information in the form of uncertain statements such as possible, most likely and almost certainly, to help and facilitate the public in diagnosing neurological diseases. Expert systems can help for disease diagnosis, where this system is to reconstruct the expertise and reasoning abilities of an expert.